THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION INTERVENTION ON DECREASING ANXIETY LEVEL AMONG HEMODIALYSIS PATIENTS IN SIDOARJO HOSPITAL - Maulana Arif Murtadho; Kusnanto Kusnanto; Lilik Herawati (Alta Dharma Publisher, 2019)
Anxiety among hemodialysis patients is often overlooked, although the psychological burden experienced can affect health and care. Progressive muscle relaxation is an effective intervention to reduce the anxiety level. This study aimed to examine the effect of continuous muscle relaxation intervention on decreasing anxiety among hemodialysis patients. A quasi-experimental, pre-test, and post-test with a non-equivalent control group was applied in this study. Seventy samples were recruited using Purposive Sampling and divided into two intervention groups and control groups. Data analysis was performed and presented in descriptive statistics, and significant findings were calculated using the paired t-test. The results of the study showed that the intervention group's anxiety level decreased from 28.76 + 4.603 to 16.61 + 2.487 after the intervention. Meanwhile, in the control group, the average anxiety level decreased slightly from 28.18 + 4.066 to 23.82 + 4.362. The paired t-test obtained a p-value of 0,000, indicating that there was a significant difference in the decrease in anxiety levels between the intervention and the control group. An intervention in progressive muscle relaxation can reduce anxiety levels in hemodialysis patients. The nurse need to consider this intervention as an alternative to reduce problem related psychological problems. Keywords: Hemodialysis, anxiety, progressive muscle relaxation